Does the Chinese government use higher education to direct globalisation? - Achtsam, Yael (2016)
The question of whether the Chinese government uses higher education to direct globalisation, is based on tranformationalist perspective of globalisation (Held et al, 1999; Mok, 2005). In this perspective it is argued that the role of the nation state might change to a more regulatory function but that ultimately nations can maintain power. This concept is explored through Chinese higher education. The selection of China is justified due to the country’s isolation policy, which has meant that it has entered the global economy later than other countries. Furthermore, on entry it has regulated and controlled national institutions, resulting in a different experience of globalisation to much of the Western discourse. Universities are examined in detail as they play a fundamental role in the identity of a nation, economy and global relations. Focus is given as to how the Chinese government has adopted a Western model but tailored this to meet economic needs of the country. In order to understand the development of higher education and the relationship with globalisation, consideration is given to historical context, economic policy and political ideology. Through this it is shown that the Chinese government does use universities to direct globalisation.